Conceptualizando la violencia y la violencia física: un análisis comparado de las legislaciones de Perú y Chile - Fernández Ruiz, José Manuel (Pontificia Universidad Católica del Perú, 2022)
This research seeks to contribute to identifying the central elements of the phenomenon of violence by conceptualizing physical violence. In this way, by identifying the elements for the concept of physical violence, it also identifies the elements for a more general conception of violence and its various manifestations. While it seems intuitively obvious what constitutes physical violence, several ambiguities appear under a more detailed examination. A simple question can illustrate this: are all homicides acts of physical violence? While an intentional homicide caused by a gunshot is an act of violence, is it also a death caused in a traffic accident? There is no obvious answer to this second question. In order to develop an answer, it is necessary first to conceptualize physical violence, but there is no specific research that clarifies its meaning. The research contributes to fill this gap in the literature, identifying elements to conceptualize what physical violence is through philosophical and comparative analysis, concluding that these elements, duly modified and particularized, can be used to understand different forms of violence.

Esta investigación busca contribuir a identificar los elementos centrales del fenómeno de la violencia a través de la conceptualización de la violencia física. De esta forma, al identificar los elementos del concepto de violencia física, también se identifican aquellos para una concepción más general de la violencia y sus diversas manifestaciones. Si bien parece intuitivamente autoevidente qué es aquello que constituye violencia física, hay varias ambigüedades que aparecen bajo un examen más detallado. Una simple pregunta puede ilustrarlo: ¿son todos los homicidios actos de violencia? Si bien un homicidio doloso causado mediante un disparo es un acto de violencia física, ¿lo es también una muerte causada en un accidente de tránsito? No hay una respuesta obvia a esta segunda pregunta. Para desarrollar una respuesta es necesario conceptualizar primero la violencia física, pero no hay investigaciones específicas que apunten a clarificar su significado. La investigación contribuye a llenar este vacío en la literatura, identificando elementos para conceptualizar qué es la violencia física a través de un análisis filosófico y comparativo, y concluyendo que dichos elementos, debidamente modificados y particularizados, pueden utilizarse para entender diferentes formas de violencia.
Conceptualizing Violence and Physical Violence: A Comparative Analysis of the Legislations of Peru and Chile
Keywords: Physical violence; Instrumental violence; Criminal law; Violencia física; Violencia instrumental; Derecho penal; https://purl.org/pe-repo/ocde/ford#5.05.01